(untitled) (Experimental biology, 2016)
The work is devoted to the existing variety of biosensors used to control environmental pollution. Provides a list of types of biosensors. The physical principles of enzymatic, microbial and DNA-sensors have been studied. Literature data about the differences in the spectrum of expressed genes in response to various pollutants. This makes it possible to create a collection of lines corresponding to a specific contaminant through the fluorescent signal of tissue and thereby realize Optosensor by higher eukaryotes. Indeed, now genetic collections P-element insertion (in particular enhancer protein and GFP-trap) of Drosophila, via which it is possible to register the activity of genes greatly. According to the conclusion that it is possible to create biosensors based on Drosophila melanogaster genetic constructs, that are similar to the properties of microbiological optosensors or exceeding their sensivity and specoficity.